Hepatic Dysfunction Caused by Consumption of a High-Fat Diet - Soltis, Anthony R. (Cell Rep, 2017)
Obesity is a major human health crisis that promotes insulin resistance and, ultimately, type 2 diabetes. The molecular mechanisms that mediate this response occur across many highly complex biological regulatory levels that are incompletely understood. Here, we present a comprehensive molecular systems biology study of hepatic responses to high-fat feeding in mice. We interrogated diet-induced epigenomic, transcriptomic, proteomic, and metabolomic alterations using high-throughput omic methods and used a network modeling approach to integrate these diverse molecular signals. Our model indicated that disruption of hepatic architecture and enhanced hepatocyte apoptosis are among the numerous biological processes that contribute to early liver dysfunction and low-grade inflammation during the development of diet-induced metabolic syndrome. We validated these model findings with additional experiments on mouse liver sections. In total, we present an integrative systems biology study of diet-induced hepatic insulin resistance that uncovered molecular features promoting the development and maintenance of metabolic disease.